2019
DOI: 10.33265/polar.v38.3461
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolamarckina pseudorjasanensis Dain, 1967 (Foraminifera) as a Kimmeridgian marker species and its significance for biostratigraphy, palaeoecology and palaeobiogeography

Abstract: This study presents a taxonomical review of the species Pseudolamarckina pseudorjasanensis Dain, 1967 collected at different sampling levels from the central and northern parts of European Russia and from Western Siberia. Morphological and biometrical analyses show that P. pseudorjasanensis is characterized by wide intraspecific variabilities and may encompass various previously described Kimmeridgian species of the genus Pseudolamarckina. The first appearance of P. pseudorjasanensis is recorded from the lates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[3].Then, the Kimmeridgian representatives of the genus Pseudolamarckina have shown that the East-European index-species Pseudolamarckina pseudorjasanensis was characterized by wide intraspecific variabilities and may encompass various previously described Kimmeridgian species of pseudolamarckiniids. The first appearance of P. pseudorjasanensis is recorded from the latest early Kimmeridgian of sub-Mediterranean and peri-Tethyan to Arctic regions [4] [5] (Figure 1(b)).…”
mentioning
confidence: 99%
“…[3].Then, the Kimmeridgian representatives of the genus Pseudolamarckina have shown that the East-European index-species Pseudolamarckina pseudorjasanensis was characterized by wide intraspecific variabilities and may encompass various previously described Kimmeridgian species of pseudolamarckiniids. The first appearance of P. pseudorjasanensis is recorded from the latest early Kimmeridgian of sub-Mediterranean and peri-Tethyan to Arctic regions [4] [5] (Figure 1(b)).…”
mentioning
confidence: 99%